Sensitization and translocation of TRPV1 by insulin and IGF-I - Pauza Mary E; Rotello Rebecca; Bhat Satyanarayan; Van Buren Jeremy J; Premkumar Louis S (SAGE Publishing, 2005)
Abstract Insulin and insulin-like growth factors (IGFs) maintain vital neuronal functions. Absolute or functional deficiencies of insulin or IGF-I may contribute to neuronal and vascular complications associated with diabetes. Vanilloid receptor 1 (also called TRPV1) is an ion channel that mediates inflammatory thermal nociception and is present on sensory neurons. Here we demonstrate that both insulin and IGF-I enhance TRPV1-mediated membrane currents in heterologous expression systems and cultured dorsal root ganglion neurons. Enhancement of membrane current results from both increased sensitivity of the receptor and translocation of TRPV1 from cytosol to plasma membrane. Receptor tyrosine kinases trigger a signaling cascade leading to activation of phosphatidylinositol 3-kinase (PI(3)K) and protein kinase C (PKC)-mediated phosphorylation of TRPV1, which is found to be essential for the potentiation. These findings establish a link between the insulin family of trophic factors and vanilloid receptors.